Peran dan Tantangan Muhammadiyah di Era Digital - Rakhman, Harianto Ghany; Ikhwan Nurdin, Syaiful; Karisma, Suhantok (Masterpiece: Journal of Islamic Studies and Social Sciences, 2025)
The digital era has brought major transformations to the Islamic education and da'wah system in Indonesia. Muhammadiyah, as one of the largest modernist Islamic organizations in the country, plays a crucial role in responding to these changes through educational reform (tajdid). This study aims to explore the role and challenges of Muhammadiyah in navigating the digital age, particularly in the context of Islamic education. A normative research method was employed, utilizing literature review and policy analysis. The findings indicate that Muhammadiyah has embraced digital technology through online learning, digital platforms, and social media da'wah. However, challenges remain, including limited digital competence among educators, the need for curriculum reform, and the negative moral impact of digital media on youth. Strategies such as strengthening human resources, technology training, and cross-sector collaboration have been implemented. With a progressive and Islamically grounded approach, Muhammadiyah has the potential to become a leading force in adaptive and excellent Islamic education in the digital era.